Polymer mediated protein crystallisation - Nikolaidi, Dimitra (2013)
Structure elucidation of a macromolecule can lead to the determination of its function. In the case of proteins, knowledge of their three-dimensional structure can be utilised in the identification of active site(s) and consequently in rational drug design. Commonly, X-ray crystallography is implemented on a high quality single crystal of the target macromolecule, in order to elucidate its structure. Moreover, crystallised protein molecules may remain active which can then be used in controlled drug delivery. Unfortunately, the successful crystallisation of a macromolecule can be seen as the most challenging aspect in this endeavour, given that predicting, screening and directing crystallisation remains an elusive goal.